Effects of intense exercise on pregnancy - a review of the literature - Weronika Kmiotek; Radosław Oronowicz; Gabriela Różańska-Smuszkiewicz; Paweł Smuszkiewicz-Różański; Aleksandra Karuś; Grzegorz Jama; Paweł Staszczak; Barbara Jaworska; Dagmara Ragan (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Purpose: We are increasingly seeing new trends on social media regarding intense strength training in pregnant women. How much should women in a physiological pregnancy exercise? The aim of this piece is to trace the guidelines and set a healthy limit for such an important aspect during pregnancy. Materials and methods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the key words: "strength training", "activity during pregnancy", "intensive exercise" and " physical activity guidelines" appropriate configurations. Conclusions: The available guidelines and medical literature show that it is worthwhile to regularly practise sport both during and in preparation for pregnancy. In a healthy, physiological pregnancy, there is a wide range of activities to choose from, through which health benefits can be achieved, such as strengthening muscles, improving performance, alleviating pregnancy complaints (constipation, pain, nausea) and improving wellbeing, and much more. However, there are contraindications to certain exercises for specific conditions during pregnancy. You should consult your doctor on a case-by-case basis.